Cadets on Campus : History of Military Schools of the United States - Coulter, John A., 1953- (Book collections on Project MUSE., 2017)
Since the founding of the United States Military Academy at West Point in 1802, more than eight hundred military schools have existed in this country. The vast majority have closed their doors, been absorbed into other educational institutions, or otherwise faded away, but others soldier on, adapting to changing times and changing educational needs. While many individual institutions have had their histories written or their stories told, to date no single book has attempted to explore the full scope of the military school in American history. Cadets on Campus is the first book to cover the or.